The effect of supervisors’ ethical leadership on graduate students’ academic procrastination in China: a moderated mediation model - Wu, Wenhao; Kulophas, Dhirapat; Xupravati, Penvara (Frontiers in Education, 2024)
Academic procrastination presents a pervasive challenge among graduate students, undermining both their academic excellence and career advancement while compromising the effectiveness and quality of university academic environments. Therefore, it is imperative to explore its antecedents to mitigate its occurrence. This research investigates the impact of supervisors' ethical leadership on graduate students' academic procrastination by employing social learning theory to construct a moderated mediation model. A comprehensive dataset was meticulously gathered from 338 graduate students using a three-stage time-lagged method, ensuring the robustness of the empirical analysis. The results of the analysis reveal a significant negative effect of supervisors' ethical leadership on graduate students' academic procrastination, with graduate students' followership mediating this relation. Additionally, graduate students' academic interests moderate the relation between followership and academic procrastination, as well as the effect of supervisors' ethical leadership on academic procrastination through the mediation of followership. The research findings offer valuable insights into the factors shaping graduate students' academic behaviors and provide practical guidance for enhancing their academic success and fostering positive academic environments in universities.